Performance Analysis of Rural Public Transportation Route Hb2 Larangan Terminal–Krian Terminal, Sidoarjo Regency - Anita Rahma Nur Iqlima; Hera Widyastuti (Publikasi Indonesia, 2025)
This study aims to identify the performance of Lyn HB2 rural public transportation that is actively operating in Sidoarjo Regency, analyze the level of satisfaction and expectations of Lyn HB2 rural public transportation users, and estimate the number of users who are willing to move from motorcycles to Lyn HB2 rural public transportation. The method used involves primary and secondary data obtained through observation and dissemination of questionnaires to Lyn HB2 rural public transportation users, as well as vehicle capacity analysis, dynamic and static surveys, and public transportation performance analysis using nine predetermined parameters. Based on the results of the existing performance, the service performance on the Lyn Hb2 Rural Public Transportation was obtained as a result that the travel time was 2 hours 22 minutes, the frequency of vehicles was 3 per hour, the load factor was 39%, with a headway time of 31 minutes, the number of trips per vehicle per day of the Lyn HB2 Rural Public Transportation as many as 3 trips.